Composite epithelial and endothelial basal laminas in human lungs. A structural basis for their separation and apposition in reaction to injury. - Huang, T. W. (1978)
A new method for electron microscopic identification of endothelial basal lamina has been developed by treating fresh human lung tissues with 5 M guanidine HCl, pH 7.2, at 20 C for 24 hours. The guanidine treatment causes significant differential swelling and substantial decrease in electron density of the endothelial basal lamina and makes the latter readily distinguishable from the epithelial basal lamina. In the thin part of alveolar septums, the unit basal lamina shared by the epithelium on one side and the endothelium on the other is found to be composed of discrete epithelial and endothelial layers in close apposition. There is no structural modification at the site of apposition. The epithelial and endothelial basal laminas in alveolar septums seem to be two independent scaffold systems with distinct structural identities despite frequent close physical contact. The findings provide a structural basis for considering separation and apposition of epithelial and endothelial basal laminas in lung reaction to injury and in the pathogenesis of alveolocapillary block.